Trade Policy and Labor Services : Final Status Options for the West Bank and Gaza - Schiff, Maurice (World Bank, Washington, D.C., 2013)
The author considers the policy options of the West Bank and Gaza with respect to trade and the export of labor services. He concludes that: 1) Nondiscriminatory trade policy is unambiguously superior to a free trade agreement with Israel; 2) The West Bank and Gaza should pursue a nondiscriminatory trade policy with all its neighbors, but only on the condition that the trade policy be open, transparent, and enforced by a credible lock-in mechanism. Otherwise, a customs union with Israel may be preferable; 3) The Palestinian Authority should establish a system of fee-based permits for Palestinians working in Israel; and 4) The Palestinian Authority should consider allowing Jordanians access to the West Bank and Gaza labor market.